A dual‐modal red‐emitting fluorescence probe for proteins based on modulation of AIE or TICT state. Issue 3 (May 2017) - Liu, Chunlin; Yang, Wei; Shen, Ping; Gao, Qingyun; Du, Jinya; Yang, Changying
Abstract: A cyanine fluorophore 2‐[4‐ N, N ‐diphenylaminostyryl]‐β‐naphthothiazolium propylsulfonate, N3, was synthesized. The asymmetric probeN3 displayed aggregation‐induced emission (AIE) characteristic in DMSO/H2 O mixtures, whereas it presented twisted intra‐molecular charge transfer (TICT) non‐emissive state in Dioxane/H2 O (Diox/H2 O) mixtures. Both the AIE and TICT state could be modulated by proteins, exhibiting switch effect. In DMSO/H2 O mixtures with 90% water fractions ( f w ), protein molecules adsorbed upon the aggregated crystalline nanoparticles ofN3 and spread over the surface, thus the strong fluorescence emission ofN3 was quenched. The different degree of quenching among proteins revealed that the adsorption of proteins onN3 aggregate particles arose from both hydrophobic and electrostatic interactions. The quenched ratio ( I 0 / I ) vs the concentration of positively protein lysozyme (Lys) gave a Langmuir type curve. In Diox/H2 O mixtures with 90% f w, the addition of bovine serum albumin (BSA) led to the reduction of non‐emissive TICT state and made the fluorescence emission ofN3 switch on. The large difference ofN3 fluorescence emission toward BSA over other proteins including human serum albumin allowed us to establish a sensitive probe for BSA. An ON‐OFF and OFF‐ON dual‐modal red‐emitting fluorescence probe for proteins was established.